Understanding the development of Th2 cell-driven allergic airway disease in early life - León, Beatriz (Frontiers in Allergy, 2023)
Allergic diseases, including atopic dermatitis, allergic rhinitis, asthma, and food allergy, are caused by abnormal responses to relatively harmless foreign proteins called allergens found in pollen, fungal spores, house dust mites (HDM), animal dander, or certain foods. In particular, the activation of allergen-specific helper T cells towards a type 2 (Th2) phenotype during the first encounters with the allergen, also known as the sensitization phase, is the leading cause of the subsequent development of allergic disease. Infants and children are especially prone to developing Th2 cell responses after initial contact with allergens. But in addition, the rates of allergic sensitization and the development of allergic diseases among children are increasing in the industrialized world and have been associated with living in urban settings. Particularly for respiratory allergies, greater susceptibility to developing allergic Th2 cell responses has been shown in children living in urban environments containing low levels of microbial contaminants, principally bacterial endotoxins (lipopolysaccharide [LPS]), in the causative aeroallergens. This review highlights the current understanding of the factors that balance Th2 cell immunity to environmental allergens, with a particular focus on the determinants that program conventional dendritic cells (cDCs) toward or away from a Th2 stimulatory function. In this context, it discusses transcription factor-guided functional specialization of type-2 cDCs (cDC2s) and how the integration of signals derived from the environment drives this process. In addition, it analyzes observational and mechanistic studies supporting an essential role for innate sensing of microbial-derived products contained in aeroallergens in modulating allergic Th2 cell immune responses. Finally, this review examines whether hyporesponsiveness to microbial stimulation, particularly to LPS, is a risk factor for the induction of Th2 cell responses and allergic sensitization during infancy and early childhood and the potential factors that may affect early-age response to LPS and other environmental microbial components.